COMPARISON BETWEEN Trachypithecus auratus AND Trachypithecus cristatus BRAIN SIZE IN INDONESIA - Endah Dwijayanti; Anang Setiawan Achmadi; Maharadatunkamsi Maharadatunkamsi; Nanang Supriatna (ZOO INDONESIA, 2020)
Taxonomic studies on Trachypithecus species in Indonesia define that this genus separated into two species that are Trachypithecus auratus and Trachypithecus cristatus with Trachypithecus auratus auratus as a subspecies. To determine relative brain size differences between species of the genus Trachypithecus in Indonesia and to examine clinal variation, a study related to brain size and morphological characters that affect the brain size is carried out. This study analyzes the brain volume between both species and examines its relationship with morphometric measurement and variables such as sex, age, and specimen location. Brain volumes were calculated from braincase volumes using 0.5 mm silica gel as mini beads. This study reveals that there are significant differences in relative brain size inter-species, sex, age and interaction among variable. Overall, T. auratus have a bigger brain size than T. cristatus, and the brain size of males are larger than females. The older individual tends to have similar brain size with younger ones. The different relative brain size on age level influenced by GSL size. Allometric body size affects the size of the brain directly. Also, there is a clinal trend in relative brain size. Trachypithecus auratus brain size is increasing from West Java to Lombok island. Further study is needed to understand the influence of external factor such as ecological and social factors on brain size in Trachypithecus.